Hydroxyphenyl‐Substituted Benzophosphole Oxides: Impact of the Intramolecular Hydrogen Bond on the Fluorescence Properties. Issue 2 (27th December 2013) - Fukazawa, Aiko; Osaki, Hiroshi; Yamaguchi, Shigehiro
Abstract Aiming at a molecule that has distinct fluorescence properties dependent on the environment of the sample, we designed and synthesized 2‐(o‐hydroxyphenyl)‐substituted benzophosphole oxides, which can form an intramolecular hydrogen bond between the hydroxy group and the phosphine oxide moiety. A 3‐phenylated derivative fluoresces in several specific solvents that have hydrogen‐bond‐accepting abilities, whereas it is virtually non‐emissive in toluene, CH2Cl2, and MeCN. Experimental and theoretical studies indicate that this trend likely results from the switching of the excited‐state character. When in weak hydrogen‐bonding solvents, the compound forms a non‐emissive excited state that results from excited‐state intramolecular proton transfer (ESIPT). In hydrogen‐bonding solvents the compound forms an emissive excited state with an intermolecular hydrogen bond between the hydroxy group and the solvent. Switching between the intramolecular and intermolecular hydrogen bonds can be a mechanism for controlling the fluorescence properties of the phosphole‐oxide‐based π‐electron systems.